Evaluating the impact of interactive video-based case-based learning in clinical medical education: a randomized controlled trial - Wang, Jing; Jiang, Yang; Fu, Xinghua; Gou, Ruiqiang; Sun, Zhijing; Li, Ge; Zhang, Wei; Nie, Jin; Wang, Wenling; Zhao, Kun; Wang, Li; Zhang, Ruihong (Frontiers in Medicine, 2025)
BackgroundTraditional Case-Based Learning (CBL) methods in clinical medical education are often hindered by limitations in scalability and student engagement. In response, interactive video-based CBL integrates decision tree scenarios with interactive technology, offering a novel approach to enhance students’ clinical reasoning and learning outcomes.ObjectiveThis study aims to evaluate the effectiveness of an interactive video-based CBL teaching method in improving clinical knowledge, thinking ability, course experience and satisfaction among undergraduate medical students.MethodsA single-center, single-blind, randomized controlled trial was conducted with 64 fourth-year clinical medicine undergraduates, who were randomly assigned to either the intervention group (interactive video-based CBL, n = 32) or the control group (traditional CBL, n = 32). The primary outcomes included basic knowledge test scores, which were assessed both before and after intervention. Secondary outcomes encompassed clinical thinking abilities (critical thinking, systematic thinking, evidence-based thinking) and course experience, measured using validated scales. Data were analyzed using paired and independent tests.ResultsSixty-two students completed the study. The intervention group showed significant improvement in post-intervention basic knowledge test scores compared to both their baseline (P < 0.001) and the control group (P < 0.001). Conversely, the control group showed a significant decline in post-intervention scores (P < 0.001). Critical and systematic thinking abilities in the intervention group significantly improved after the intervention (P = 0.045 and P = 0.048), while no significant changes were observed in the control group. No significant changes were observed in evidence-based thinking. Course experience scores were significantly higher in the intervention group across dimensions including good teaching (P = 0.041), classroom quality (P = 0.033) and classroom gains (P = 0.032). The intervention group was significantly more satisfied than the control group overall (P = 0.011).ConclusionInteractive video-based CBL significantly enhances basic knowledge, critical thinking, and students’ course experience and satisfaction compared to traditional CBL, highlighting its potential as an innovative teaching method in clinical medical education. Further research is needed to explore its long-term impacts and optimize its application for fostering evidence-based thinking.Clinical trial registrationhttps://clinicaltrials.gov/, identifier ChiCTR2300073773.